A general approach to cobalt-based homobimetallic phosphide ultrathin nanosheets for highly efficient oxygen evolution in alkaline media. Issue 4 (31st January 2017) - Xiao, Xiaofen; He, Chun-Ting; Zhao, Shenlong; Li, Jing; Lin, Wensheng; Yuan, Zhongke; Zhang, Qiang; Wang, Shuangyin; Dai, Liming; Yu, Dingshan
Abstract : A general and effective approach was proposed to fabricate a new family of Co-based bimetallic phosphide ultrathin nanosheets for highly-efficient oxygen evolution. Abstract : A general and effective approach was proposed to fabricate a new family of Co-based bimetallic phosphide ultrathin nanosheets (CoM-P-NS, M = Ni, Mn, Cu, Zn) with homogeneous composition and unique porous architecture using ultrathin metal–organic framework nanosheets (MOFNs) as precursors for the first time, which yielded synergistically active sites, mass transport and dynamic modulations for the oxygen evolution reaction (OER). The optimized samples showed remarkable oxygen evolution activity in alkaline electrolytes, outperforming both the commercial RuO2 and Ir/C benchmarks and ranking the best among all the metal-phosphide electrocatalysts reported to date.